The Problems Associated with Preparation of Disaggregated Information - Karwowski, Mariusz (Olsztyn Economic Journal, 2014)
In this article the author discusses the problems associated with the preparation of disaggregated information. These problems include: identification of segments, measuring segment profitability, internal prices, and measuring segment assets.